Reporting on Sustainable Development Goals. A Score-Based Approach with Company-Level Evidence from Central-Eastern Europe Economies - Elena-Mirela Nichita; Elena Nechita; Cristina-Lidia Manea; Diana Manea; Alina-Mihaela Irimescu (Journal of Accounting and Management Information Systems (JAMIS), 2020)
Research Question: Which chemical companies from CEE countries are pioneers in both disclosing SDGs achievements and progressing in fulfilling self-imposed targets? Motivation: Revealing SDGs is unfruitful if it is not supported by relevant indicators to highlight progress against targets (EY, 2017; Schramade, 2017). The strategic importance of the chemical industry, one of the most diversified from all industries, creates sound circumstances for this sector to make known all efforts and contributions towards sustainability engagements (Aga, 2012; Zimara & Eidam, 2015). Idea - Beside financial reporting, currently businesses are encouraged to publish non-financial information to express their awareness about nature and human capital. The chemical industry should consider the SDGs a catalyst for significant business opportunities and a contributor for a better life, across sector and through cooperation with other sectors. Data: In this paper we used a set of panel data extracted from non-financial reports and websites of the 10 largest companies in the chemical industry operating in countries from Central-Eastern Europe: Czech Republic, Hungary, Poland, Romania, and Slovakia. Our analysis covers the period 2015-2019 and addresses the disclosure and progress on reporting SGDs. Tools - To assess the degree of disclosure regarding SDGs and the advancement alongside companies' efforts to comply with UN goals, we carried out a textual and content analysis, then we developed a score, with qualitative and quantitative features, to deliberate the disclosure of SDGs information incorporated in reports. Findings - Our discoveries indicate that 63% of the analysed reports did not clearly mention the SDGs that were targeted by companies' investments. This result noticeably points out that SDGs reporting is presented relatively dissimilar, with reference to structure and extent, among the analysed companies, even though they are part of the same industry. Contribution: We consider this paper may be valuable to scholars in their journey considering, assessing and developing original approaches in regard to researches about non-financial reporting, in general, and SDGs, in particular, nevertheless, to businesses to advance in their accomplishments and reporting on the topic of SDGs.
Keywords: M14; M21; Q01; Q56; 650; Sustainable Development Goals (SDGs); chemical industry; Central-Eastern Europe (CEE) economies; score-based approach; content analysis; non-financial reporting; disclosure